2002
DOI: 10.1128/cdli.9.5.972-982.2002
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of the Lipopolysaccharide-Neutralizing Activities of Human Cathelicidin CAP18/LL-37-Derived Antimicrobial Peptides by Replacement with Hydrophobic and Cationic Amino Acid Residues

Abstract: Mammalian myeloid and epithelial cells express various peptide antibiotics (such as defensins with three K residues, the cationicity of the peptide (18-mer LLKKK) was enhanced. Among peptide derivatives, 18-mer LLKKK displayed the most powerful LPS-neutralizing activity: it was most potent at binding to LPS, inhibiting the interaction between LPS and LPS-binding protein, and attaching to the CD14 molecule, thereby suppressing the binding of LPS to CD14؉ cells and attenuating production of tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
159
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(165 citation statements)
references
References 56 publications
(98 reference statements)
6
159
0
Order By: Relevance
“…However, LL-37 has a broader spectrum concerning the antimicrobial activity and is moreover able to induce neovascularization 15 and to demonstrate binding of bacterial endotoxin (LPS, minimal active concentration: 12.5 mg/ml) 14 or chemotactic activity for neutrophils, monocytes 33 and mast cells (effective concentration 1-10 mM). 32,34 Finally, regarding the actual resistance problem of classic antibiotics and its rapid progress, it must be mentioned that there is only a very low tendency of developing resistance to HDP. 35,36 Possible systemic side effects after systemic or local applications of LL-37 still remain a field for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, LL-37 has a broader spectrum concerning the antimicrobial activity and is moreover able to induce neovascularization 15 and to demonstrate binding of bacterial endotoxin (LPS, minimal active concentration: 12.5 mg/ml) 14 or chemotactic activity for neutrophils, monocytes 33 and mast cells (effective concentration 1-10 mM). 32,34 Finally, regarding the actual resistance problem of classic antibiotics and its rapid progress, it must be mentioned that there is only a very low tendency of developing resistance to HDP. 35,36 Possible systemic side effects after systemic or local applications of LL-37 still remain a field for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the C-terminal domain of hCAP18 could neutralize various activities of LPS [20,24,34] and LTA [34]. Nagaoka et al [24] identified an 18-mer peptide derived from hCAP18/LL-37, which is also included in our 22-mer peptide. By modifying hydrophobicity and cationicity of this peptide they could augment LPS neutralizing activities of this peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide solutions were diluted 1:100 with acetonitrile/ water/TFA 50/50/0.2 (v/v/v) and 1 ml of each solution was mixed with 1 ml of a 10 mg/ml solution of a-cyano-4-hydroxycinnamic acid (4-ACH) in acetonitrile/water/TFA 50/50/0.2 (v/v/v) containing a mass reference peptide (VNTPEHVV-PYGLGSPSRS, bovine big-endothelin (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), MH av + = 1897.10).…”
Section: Maldi-tof Mass Spectrometry Analysismentioning
confidence: 99%
“…LL37 has broad spectrum activity against Gram-positive and Gramnegative bacteria including antibiotic-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and fungi [74,90,91,97,98]. In addition to bactericidal activity, LL37 is able to bind to LPS and neutralize its endotoxin activity [89,99,100], and acts as a chemotactic factor for neutrophils, monocytes, T cells, and mast cells [90,101,102].…”
Section: Defensinsmentioning
confidence: 99%